Examination of the Diameter of the Rectum and the Thickness of the Anterior Wall of the Rectum by Ultrasound in Children With Chronic Constipation and Abdominal Pain in the Age Range of 2–18 Years - Mitra Azra Aldaghi; Nafiseh Shourideh Yazdi; Mohammad Esmail Ahmad Abadi; Rahil Mahmoudi; Hadi Lotfi (JGH Open)
ABSTRACT Abdominal pain is one of the most common complaints to the pediatric clinic and can be challenging for the physician. Among children who present with abdominal pain, constipation is one of the main causes of abdominal pain, and its incidence in childhood is estimated at 1%–30%. Materials and Methods Hundrerd children with chronic constipation, defined according to the Rome IV constipation criteria, who were referred to Sabzevar Children's Clinic, were included in the study. Hundred people in the control group were selected from children without constipation who underwent abdominal ultrasound due to abdominal pain. Consent was obtained from the children's parents, and the child's consent was also obtained for ultrasound. Rectal diameter and rectal anterior wall thickness were measured by an experienced radiologist. Results The results determined that the diameter of the rectum measured by ultrasound in children with constipation is greater than in the control group. Also, the thickness of the rectum was lower in children with constipation compared to the control group. It was found that there was no significant relationship between gender and constipation in children. There was a significant relationship between constipation in children and their body mass index (BMI) and age. The results of the study showed that there was no significant relationship between history of urinary tract infection and constipation and socioeconomic status in children. There was a significant relationship between the diameter of the rectum and the duration of constipation. Discussion Ultrasound can be useful in diagnosing children with constipation in whom it is difficult to take a history and physical examination.